The administrative jurisdictional activity in the sphere of land use and conservation: Russian Federation experience - Городецька, Ірина Альбінівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2011)
Russian Federation experience of administrative jurisdictional activity in the sphere of land use and conservation and the possibility of its usage in the activity of a sate inspector on land use and conservation in Ukraine are analyzed in the article.